Efektivitas Chlorhexidine sebagai Inhibitor MMP-2 dan MMP-9 dalam Proses Dermonekrosis Akibat Racun Kumbang Tomcat (Paederus sp.) (The Effectiveness of Chlorhexidine as MMP-2 and MMP-9 inhibitor in Dermonecrotic Process due to Rove Beetles Toxin (Paederus sp.)) - Putri Erlinda Kusumaningarum; Al Munawir (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Paederus dermatitis is dermonecrotic condition caused by Rove beetles (Paederus sp.). Paederin toxin come from endosymbiotic between rove beetles and Pseudomonas aeruginosa and can produces MMP-2 and MMP-9. Chlorhexidine is expected to be alternative therapy and prevention of dermatitis paederus due to it's MMP inhibitor and bacteriostatic effect. The study aimed to investigated the effectivity of chlorhexidine as MMP-2 and MMP-9 inhibitor in dermonecrotic process due to rove beetles toxin. Research groups consisted of negative control (paederin toxin), treatment 1 (paederin toxin + chlorhexidine 0,012%), treatment 2 (paederin toxin + chlorhexidine 0,06%), treatment 3 (paederin toxin + chlorhexidine 0,3%), and normal control (aquadest). As much as 9,3 µg paederin toxin and chlorhexidine are injected to the well of 8% acrylamide gel containing gelatin. Measuring of band density using ImageJ showed a decreasing of MMP-2 and MMP-9 band density. Negative control group was considered to have 1 of relative optical density. The result showed that chlorhexidine 0,06% can inhibits 21,6% MMP-2 activities and at 0,3% can inhibits 16,4% MMP-9 activities. One way ANOVA test show different significantly between negative control and treatment group (p<0,05). In conclusion chlorhexidine has potency as MMP-2 and MMP-9 inhibitor in dermonecrotic process due to Rove Beetles toxin. Keywords: Rove beetles(Paederus sp.), dermonrcrotic, MMP-2, MMP-9, chlorhexidine